Peran Transparansi Financial Decision dalam Memediasi Pengaruh Financial Attitude terhadap Financial Well-Being (Penerima KIP Kuliah) - Syahrul Nasarudin; Mira Mira; Masrullah Masrullah (Jurnal Riset Akuntansi Politala, 2026)
This study aims to analyze the mediating role of financial decision transparency in the relationship between financial attitude and financial well-being among KIP Kuliah recipients at Universitas Muhammadiyah Makassar. As a government-funded educational assistance program, KIP requires responsible financial management to enhance students’ financial well-being. However, positive financial attitudes do not automatically lead to financial well-being without transparent financial decision-making practices. This study employs a quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Primary data were collected through questionnaires distributed to KIP recipients. The analysis included validity, reliability, and hypothesis testing using bootstrapping techniques. The results indicate that financial attitude has a significant positive effect on financial decision transparency. Financial decision transparency also has a significant positive effect on financial well-being. Furthermore, financial decision transparency partially mediates the relationship between financial attitude and financial well-being. These findings suggest that students’ financial well-being improves when positive financial attitudes are translated into transparent and accountable financial decisions.